from the first linear equation:
x = 3 - 2y
plug that into
2y^2 + 3x^2 + 4xy = 9
2y^2 + 3(3-2y)^2 + 4y(3-2y) = 9
2y^2 + 27 - 36y + 12y^2 + 12y - 8y^2 -9 = 0
6y^2 - 24y + 18 = 0
y^2 - 4y + 3 = 0
(y - 1)(y - 3) = 0
take it from there
can u solve x and y simalteneously for me thanks in advance x-3+2y=0 2y^2+3x^2+4xy=9
3 answers
from this step how did u come up with 2y^2+27-36y+12y^2+12y-8y^2-9=0
I expanded the 3(3-2y)^2 part
= 3(9 - 12y + 4y^2
= 27-36y+12y^2
straightforward algebra
= 3(9 - 12y + 4y^2
= 27-36y+12y^2
straightforward algebra